The Effect of Gamma Ray Irradiation on the Growth of Bendy Variety-Green Okra (Abelmoschus esculentus L.) - Yuti Ariyanti; Kamsia Dorliana Sitanggang; Yusmaidar Sepriani; Fitra Syawal Harahap (Universitas Labuhanbatu, 2024)
Widely cultivated, green okra (Abelmoschus esculentus L.) is a highly profitable horticultural crop. In contrast, okra production has not shown any significant improvement. This study observed the growth of green okra (A. esculentus L.) plants using gamma rays. In this investigation, the nonfactorial Randomised Block Design (RBD) method with three replications was implemented to investigate the effect of gamma radiation on green okra (A. esculentus L.) seeds. The study examined six levels of gamma radiation: 0 Gy (control), 100 Gy, 300 Gy, 500 Gy, 700 Gy, and 900 Gy. The findings indicated that plants demonstrated a survival rate at a dose of 0 Gy. At the same age, the irradiation dose of 700 Gy resulted in the highest number of leaves, whereas the control dose of 0 Gy resulted in the lowest number of leaves. The irradiation treatment dose of 500 Gy exhibited the least flowering time, while the control dose of 0 Gy exhibited the fastest flowering time. The slowest flowering time was observed at 900 Gy. This investigation determined that, compared to other radiation levels, gamma radiation at 2 WAP exhibited substantial radiation levels. This study demonstrates the critical role of gamma radiation at 2 WAP in okra production. The results of this study can be used as a prerequisite for ensuring the highest quality offspring from the effects of gamma radiation